2011
DOI: 10.21273/hortsci.46.2.324
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Carbon Footprints of Organic Orchard Production Systems to Address Carbon Trading: An Approach Based on Life Cycle Assessment

Abstract: Carbon footprint is widely accepted as an indicator of greenhouse gas emissions and global warming. Modeling carbon footprints based on life cycle assessment is applied as a way to evaluate the net contribution of greenhouse gases to the atmosphere from orchard production systems over one growing year. This net balance approach considers the sources and sinks of carbon and therefore provides a better reflection of an orchard system's net contribution to climate change. Carbon footprinting of organic ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 10 publications
5
13
1
Order By: Relevance
“…The total net C sink from apple orchards in China is about 27 Tg C in 2010, which is equivalent to 14 t C ha −1 . If taking the life cycling of apple trees as 25 years, the figure is similar to the reported amount for organic kiwifruit and apple production systems in New Zealand [30] . It is predicted that the capability continues growing substantially in China in the future because of the increase of growing areas and more apple orchards entering the mature stage.…”
Section: Discussionsupporting
confidence: 68%
“…The total net C sink from apple orchards in China is about 27 Tg C in 2010, which is equivalent to 14 t C ha −1 . If taking the life cycling of apple trees as 25 years, the figure is similar to the reported amount for organic kiwifruit and apple production systems in New Zealand [30] . It is predicted that the capability continues growing substantially in China in the future because of the increase of growing areas and more apple orchards entering the mature stage.…”
Section: Discussionsupporting
confidence: 68%
“…It is nevertheless important to estimate the contribution of orchards, especially in regions where they are highly concentrated. Studies have shown that fruit orchards such as kiwifruit, apple, peach, orange and olive could sequester from 2.4 to 12.5 t C/ha/year (Sofo et al 2005;Page et al 2011;Montanaro et al 2017). Orchards may sequester quantities of carbon similar to those of forests during their first years of life since photosynthesis activity is greater in young trees than in older ones (Wu et al 2012).…”
Section: Climate Regulation: Mitigation Of Greenhouse Gas Emissionsmentioning
confidence: 99%
“…Furthermore, in most cases, carbon in fruit trees is only temporarily sequestered since the lifespan of an orchard ranges from 15 to 30 years and the trees are usually burned without any valorization at the end of their lives. Life cycle analyses show that carbon emissions may also come from other sources: CO 2 emissions by engines during weeding or fertilization might represent as much as 23% of total CO 2 emissions in intensive apple orchards (Page et al 2011). It is therefore important to precisely quantify these losses.…”
Section: Climate Regulation: Mitigation Of Greenhouse Gas Emissionsmentioning
confidence: 99%
See 2 more Smart Citations